Sosialisasi Sistem Informasi Akuntansi Pesantren Di Pondok Pesantren Modern Assuruur Kabupaten Bandung - Tri Utami Lestari; Ruri Octari Dinata; Hilda Salman Said (Berdikari: Jurnal Pengabdian Masyarakat Indonesia, 2022)
Islamic boarding schools called “pesantren” grow and develop funded from various sources such as waqf, infaq and alms, dues or donations from the parents of students, and others. Therefore, the principle of accountability in carrying out educational activities in Islamic boarding schools is very important. There are two institutions, namely BI and IAI that have developed guidelines and accounting principles that are suitable to be applied in Islamic boarding schools. BI issued Pedoman Akuntansi Pesantren, and IAI has provided PSAK 101, PSAK 112 and ISAK 35 which can also be used by Islamic Boarding Schools. The purpose of this community service activity is to help socialize the importance of building an accounting information system so that the implementation of Islamic boarding school bookkeeping can comply with existing regulations to produce accountable financial reports. The socialization activities are carried out using an implementation approach, with activities in the form of needs analysis, implementation of socialization, and evaluation. Feedback from participants on this activity was carried out after the event took place. From the survey conducted, there were 57% and 38% percent of participants who stated strongly agree and agree on the importance of this activity being held in providing an understanding of accounting information systems in Islamic boarding schools.